Public Health Perspective on UK-identified Victims of Modern Slavery. (December 2021) - Bird, Sheila
Links between identified-victims, which occur if escape of one has led to rescue of others (as cluster of victims in single location or controlled-individuals across a network of locations), have implications for how the totality of victims of modern slavery is estimated. Information from identified-victims can help to identify densely or dangerously trafficked-routes. Vulnerability of victims is not ended by their liberation: evidence-based healthcare and other support protocols are needed to assist recovery and resilience. The evidence-base for national protocols would be enhanced if over half the identified-victims agreed to join a research-led cohort by which morbidity and mortality could be monitored; location notified if the participant was again in extremis; with DNA-sampling offered as means to re-unite trafficked family-members.